MASALAH DEMOGRAFIS DAN KEBIJAKAN PEMERINTAH PROVINSI KEPULAUAN RIAU - Anna Triningsih (Research Centre for Population, Indonesian Institute of Sciences, 2013)
The rate of population growth that significantly transpires in the Riau Islands Province will certainly bring an impact that is quite complex on the social and economic problems, such as high unemployment, and criminality. There are three demographic factors that affect the rate of population growth; fertility, mortality and migration. Anticipatory measures should be taken by the local government of the Riau Islands province in order to anticipate problems that will arise through harmonized policies both of which deal with the institutional aspects as well as the substance of the policy that will be applied. This paper is based on the 2010 study in the Riau Islands Province. By using the approach of both quantitative and qualitative studies, the data excavation in the study is done by the distribution of questionnaires and the interview of stakeholders. Afterwards, the data collected will be analyzed using content analisys method The results of this study formulate several recommendations for policies that address the issues of family planning, the prevention of the spread of HIVI AIDS and the harmonization of control of the migration population.Keywords: Formulation, Policies, Local Government, Harmony, Population Development, and Family Development